PEMBELAJARAN METODE KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR BAHASA ARAB (QOWAâID) MAHASISWA PERBANKAN SYARIâAH IAIM NU METRO LAMPUNG TAHUN 2017 - Syaifullah, Muhammad (Jurnal Bahasa Lingua Scientia, 2017)
Learning Arabic qowaid student Syariah Banking Second semester Maarif Institute of Islamic NU Metro Lampung still not maximized. Students have difficulties to understand Arabic qowaid material. Student learning motivation is also low. This is what makes researchers want to do research in that class. Problems to be expressed in this research are: (1) How is the application of Arabic qowaid learning with cooperative model of jigsaw method in class A, second semester of Syariah Banking, (2) How to improve learning qowaid after getting learning with cooperative learning model of jigsaw method, (3) What are the advantages and disadvantages of implementing cooperative Arabic qawaid in class A with jigsaw method. This research is a classroom action research conducted in two cycles. Each cycle is done in a cycle consisting of four stages: planning, execution, observation and reflection. The results of this study indicate an increase from cycle I of cycle II. The average class cycle I is 60.83 and the average of cycle II is 71. The students also show behavior change in the positive direction. Student activity is increasing. The improvement of test result is also followed by behavioral and motivational change based on research which has been done by the researcher that through cooperative learning with jigsaw method, Arabic qowaid learning becomes more fun and easier for students in learning qowaid. Suggestions that can be given is a lecturer of Arabic language should be more creative in using techniques and learning methods that involve the active role of student learning so that the learning process to get the maximum value. One alternative of learning Arabic qowaid is by using cooperative learning jigsaw model.